2022
DOI: 10.3389/fpubh.2021.735624
|View full text |Cite
|
Sign up to set email alerts
|

What Are We Measuring When We Evaluate Digital Interventions for Improving Lifestyle? A Scoping Meta-Review

Abstract: Background: Lifestyle Medicine (LM) aims to address six main behavioral domains: diet/nutrition, substance use (SU), physical activity (PA), social relationships, stress management, and sleep. Digital Health Interventions (DHIs) have been used to improve these domains. However, there is no consensus on how to measure lifestyle and its intermediate outcomes aside from measuring each behavior separately. We aimed to describe (1) the most frequent lifestyle domains addressed by DHIs, (2) the most frequent outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 131 publications
0
8
0
Order By: Relevance
“…While the gold standard for evaluating a health intervention is conducting a randomized controlled trial, these can take a long time and typically require many participants and extensive financial resources. Long delays to evaluate novel digital interventions in the rapidly evolving field might result in the digital interventions becoming obsolete or nonfunctional by the time the trial is completed [ 73 ]. Thus, the evaluation of digital interventions potentially requires new study designs and methods that take the iterative and rapidly evolving nature of such interventions and continuous data collection into account.…”
Section: Discussionmentioning
confidence: 99%
“…While the gold standard for evaluating a health intervention is conducting a randomized controlled trial, these can take a long time and typically require many participants and extensive financial resources. Long delays to evaluate novel digital interventions in the rapidly evolving field might result in the digital interventions becoming obsolete or nonfunctional by the time the trial is completed [ 73 ]. Thus, the evaluation of digital interventions potentially requires new study designs and methods that take the iterative and rapidly evolving nature of such interventions and continuous data collection into account.…”
Section: Discussionmentioning
confidence: 99%
“…According to recent statistics, the Health and Fitness category accounts for a large proportion of apps in both the Android and Apple app stores—the eighth-largest categories of apps ( 35 ). Previous literature has shown that smartphone app usage is one of the most frequently used methods of digital health interventions for enhancing physical activity ( 36 ), and the use of apps can increase cognitive patterns encouraging exercise and physical activity, so those who use fitness apps participate in significantly more physical activity than those who do not ( 37 ). A growing literature recognizes the positive effects of exercise on emotional states such as anxiety, stress and depression, including helping people with mood disorders achieve better mental health outcomes ( 38 ).…”
Section: Theoretical Underpinning and Hypothesis Developmentmentioning
confidence: 99%
“…Here, we focus on two. First, recent perspectives highlight the importance of tracking multi-modal vs. single risk factors [12] for a more comprehensive lens into an individual's metabolic health profile [20]. However, the extent to which different studies focus on one vs. more risk factors in digital metabolic health contexts remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…These include lifestyle determinants (i.e., nutrition, physical activity, sleep, stress, and substance abuse) and physiological markers (i.e., blood sugar, triglycerides, and HDL cholesterol) [6–10]. Following a complex systems perspective, modifiable factors interact dynamically [11] and together shape disease outcomes over time, with up to 70% of cardiovascular disease cases and mortality attributed to modifiable risk factors [12] [9].…”
Section: Introductionmentioning
confidence: 99%